Analysis of Investment Performance of Malaysia’s Stock Market During Covid-19 Pandemic - ZAMRI, MUHAMMAD AFDAL HAKIM; Ismail, Ts. Dr Isaudin (Enhanced Knowledge in Sciences and Technology, 2023)
This study aims to examine the investment performance of stocks market in Malaysia using Sharpe, Treynor and Jensen’s alpha method, to obtain the evaluation value of each stock market’s performance in Malaysia by using Sharpe, Treynor and Jensen’s alpha method and to determine the effect on COVID19 to the stock market’s enactment in Malaysia with considering the effect of COVID-19 pandemic to the several sectors and industries. This research uses the quantitative method where the timeframe needed before the pandemic is between March 1, 2019 and February 29, 2020 while for after the pandemic is between March 1, 2020 and February 28, 2021. The research data samples that obtained then refined by using SPSS software and Microsoft Excel. It will be refined by using z-score transformation because the three methods have different properties. After that, the data that undergoes z-score transformation will be refined by using Kruskal Wallis Test for the decision making whether there are notable difference in the portfolio performance and lastly, the T-test method is used to determine whether there are notable difference in the ratios data for the Pre-COVID19 and During COVID19. The results of this study is some of the stocks will have the low performance with compared to the other stocks by using Sharpe, Treynor and Jensen’s method.